Frequency agile microstrip antenna symmetrically loaded with tunnel diodes - Qautam A.K.; Vishvakarma B.R. (My University, 2025)
A new technique for designing the frequency agile microstrip antenna is presented. The frequency agility is achieved by symmetrical loading of two identical tunnel diodes in which the operating frequency of the rectangular microstrip antenna is electronically controlled by the bias voltage of tunnel diodes. Theoretical modal for an antenna is developed using modal cavity model and result are also simulated with MOM-based simulator. The tuning range is found to be 55.92 MHz (6.67%), which is much better than earlier reported data. Antenna shows consistant return loss and radiation pattern for entire tunable frequency range. © 2006 Wiley Periodicals, Inc.